Unexpected hemorrhage of a rare vessel, a pubic branch of the external iliac artery, after laparoscopic radical prostatectomy: Case report. Issue 50 (December 2017) - Jiang, Wei-Xing; Zhou, Zhi-En; Yan, Wei-Gang; Pan, Jie; Ji, Zhi-Gang
Abstract: Rationale: Postoperative hemorrhage is a rare complication after laparoscopic radical prostatectomy (LRP), with no case reports of bleeding from the external iliac artery in the literature. Patient concerns: A 73-year-old man diagnosed with clinical stage 2c prostate cancer underwent LRP successfully with only approximately 200 mL of intraoperative blood loss. However, his blood pressure dropped from 135/74 to 80/49 mm Hg and his hemoglobin decreased by 66 g/L compared with the preoperative level within 5 hours. Diagnoses: Active hemorrhage from a pubic branch of the external iliac artery was found by digital subtraction angiography (DSA). Interventions: The patient was treated with superselective intraarterial embolization. Outcomes: The bleeding stopped and the patient recovered uneventfully with no further hemorrhage or other complications. Lessons: Although postoperative hemorrhage after LRP is exceptionally rare, it can occur not only in the internal iliac artery but also in the external iliac artery. In addition, contracted pelvis cases should be addressed with more caution by the laparoscope holder in case external iliac artery is injured.